Lived Social Sufism beyond Institutions: Non-Institutional Charismatic Authority in Contemporary Indonesian Islam - Muniron Muniron; Fidia Astuti; Faiz Marikar (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2025)
This study examines the life of KH Dauglas Toha Yahya (Gus Lik) as a contemporary expression of non-institutional social Sufism in Indonesia. Over the past two decades, the rise of symbolic religiosity, the popularity of celebrity preachers, and the commodification of religion have created a gap between outward religious expressions and substantive forms of social piety. This study aims to explain how Gus Lik’s everyday practices present an alternative model of religiosity rooted in simplicity, social proximity, and service to the community. Using a qualitative design and a historical–hermeneutic framework, the study draws on in-depth interviews, participant observation, and document analysis. The data were analyzed using content and thematic analysis. The main findings identify three central patterns: first, Sufi asceticism (zuhud), manifested in a minimalist lifestyle, rejection of wealth and privileges, and closeness to marginalized groups; second, ta’dzim toward one’s teacher, which forms moral ethos, emotional discipline, and non-institutional charismatic authority; and third, khidmah (social service), reflected in direct engagement with the community, the formation of horizontal solidarity, and the creation of inclusive religious spaces. The study’s implications indicate that these Sufi values can play a significant role in strengthening social cohesion, offering critique against the commodification of spirituality, and presenting a model of religious leadership grounded in ethical exemplarity. The originality of this study lies in its systematic mapping of a contemporary Sufi figure who has received limited scholarly attention, as well as the formulation of a typology of “social Sufism” as a theoretical contribution to religious studies in Southeast Asia.